2020 ASEE Virtual Annual Conference Content Access Proceedings
DOI: 10.18260/1-2--34642
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Impacts of a Flipped-instruction Mode for a Disciplinary Computer Applications Course

Abstract: also in Mechanical Engineering. He currently teaches first-year engineering courses as well as various courses in Mechanical Engineering, primarily in the mechanics area. His pedagogical research areas include standards-based assessment and curriculum design, including the incorporation of entrepreneurial thinking into the engineering curriculum and especially as pertains to First-Year Engineering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Some comments on the post-course survey revealed a desire to pursue more than one topic exploration, suggesting that the project could be extended to include two topics during future iterations of the course. Freedom to explore content and pass assessments at an individual pace is a characteristic of competency-based course assessments [16,17]. The positive response of students to this independent style of learning further suggests that the 3DM course could be a strong candidate for competency-based assessment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some comments on the post-course survey revealed a desire to pursue more than one topic exploration, suggesting that the project could be extended to include two topics during future iterations of the course. Freedom to explore content and pass assessments at an individual pace is a characteristic of competency-based course assessments [16,17]. The positive response of students to this independent style of learning further suggests that the 3DM course could be a strong candidate for competency-based assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Under such a model, students would set their own weekly learning goals throughout the semester. Highly experienced students could focus more on the advanced skills while less confident students could spend additional time addressing introductory and intermediate skills [16].…”
Section: Discussionmentioning
confidence: 99%
“…In Spring of 2019, the course was moved to a flipped instruction mode. The details and impacts of this model were previously discussed [12]. To summarize, this iteration of the course utilized a series of short instructional videos, assigned in small batches on a weekly basis and accompanied with a short one-to-two question quiz relating to the video content.…”
Section: Context and Course Progressionmentioning
confidence: 99%
“…The daily work component of the course (making up 10% of the overall grade) consists of a combination of weekly modules, in-class activities, and journals. The weekly modules are the flipped video modules previously discussed and the associated one-question quizzes that accompany them [12]. Generally, modules are assigned in groups of 3-5 and are due every Monday for most of the term.…”
Section: Daily Workmentioning
confidence: 99%
“…
The best paper in the Mechanical Engineering Division at the 2022 ASEE Annual Meeting in Minneapolis showed that student learning increased with weekly quizzes rather than daily homework. 1 The authors' work built on several recent papers showing that mastery learning with multiple attempts at each quiz increased student success. [2][3][4] Engineering Statics at NC State University has long included daily homework assignments, so the pivot to weekly quizzes will need to be adopted over multiple semesters and adopted for large enrollment sections.
…”
mentioning
confidence: 99%